Priorities for the minority? Street-based sex work and Partnerships and Communities Together (PACT). (September 2013) - Sagar, Tracey; Jones, Debbie
The 2006 Co-ordinated Prostitution Strategy recommended local 'needs'-based responses to target street sex work, and to this end consultation with members of the wider community – an approach that has also been more recently recommended by the current Coalition government in 2011. This article draws on empirical data collated over two years in the city of Cardiff, Wales. It focuses on Partnerships and Communities Together (PACT) meetings as a primary pathway for police/public consultation, and highlights how despite a lack of community representation at PACT, street sex work can become a community priority to be addressed with a punitive response. However, a public opinion survey carried out with 205 Cardiff residents suggests the wider community are more tolerant and very concerned about the safety of street workers. In conclusion we suggest that PACT priorities can misinterpret and misrepresent the views and opinions of the community.